PENYIMPANGAN SOSIAL DALAM PRILAKU SEKS BEBAS DIKALANGAN REMAJA - Syahrul Akmal Latif; Muhammad Zulherawan (UIR PRESS, 2019)
Social deviations in free sex behavior among adolescents is quite alarming because they are seen as bad behavior and contrary to the norms in society. The purpose of this study is to seek solutions to the problem of social deviations of free sex among adolescents by looking at the factors and things that underlie free sex behavior that occurs by departing from theological and sociological analysis and also using the Differential Association theory by Sutherland which explains the process of occurrence deviant behavior. In this study the authors use the method of literature study of various thoughts and previous studies that have been conducted. As for the discussion of this study, the writer took three discussions which became an outline for the author, namely: 1. Knowledge of adolescents about free sex, 2. Free sex behavior among adolescents, and 3. Factors causing free sex among adolescents. So based on this research it is expected to be a solution for the political elite, government, academics and society especially parents to be more together to protect teenagers from the influence of the phenomenon of free sex among adolescents.